Developing an Appropriate Goalball Unit for Secondary Physical Education - Laughlin, Michael K.; Happel, Kathleen (Strategies, 2016)
Goalball, a sport designed for those with visual impairments, is a competitive and recreational sport enjoyed by athletes around the world. Students with and without visual impairments can experience positive outcomes when teachers appropriately include a goalball unit as part of their inclusive secondary physical education curriculum. This article aims to help teachers identify these outcomes through strategies that encourage student success and appreciation for the sport. A framework to implement a goalball unit is provided along with strategies to target skill, tactical and game-play development.
_eprint: https://doi.org/10.1080/08924562.2015.1111784
Keywords: dept.hms